Determinants of transparency in Inland revenue board of Malaysia - Nor Aizarina, Mat Isa (2018)
Tax administration transparency is an essential feature of democratic governance. The moral essence of transparency lies in the fact that people have a right to information, which in turn allows them to assess the relevance of the procedures and the decisions made by the government. A transparent tax administration is very important in managing a nation’s revenues within a legally-approved tax system in order to enhance public confidence. There are extensive studies on tax administration globally; however there are very limited studies on tax administration transparency in Malaysia. This study looks into the determinants of transparency in Inland Revenue Board of Malaysia (IRBM) as the direct tax administrator of the country and includes autonomy, information and communication technology (ICT), culture and external publication as the factors determining transparency. This study is supported by theory of transparency which assumes that information, once set free from the state that creates it, will produce an informed and engaged public and as well will hold officials accountable. The data was collected through survey questionnaires and analysed using multiple regression analysis and other statistical techniques. A total of 375 questionnaires were distributed that yielded 185 usable questionnaires. The results reveal that there is a positive and significant relationship between autonomy, ICT, and culture with transparency of IRBM. However external publication is found as having a positive but insignificant relationship with transparency of IRBM. This study concludes with the theoretical implications and practical recommendations for IRBM as the direct tax administrator to look into the autonomy status, implementation of ICT and organizational culture in order to achieve a satisfactory level of transparency locally and internationally. This study also highlights several limitations and suggests future studies in this area.